Spinal CXCL9 and CXCL11 are not involved in neuropathic pain despite an upregulation in the spinal cord following spinal nerve injury. Issue 1 (May 2018) - Wu, Xiao-Bo; He, Li-Na; Jiang, Bao-Chun; Shi, Hui; Bai, Xue-Qiang; Zhang, Wen-Wen; Gao, Yong-Jing
Chemokines-mediated neuroinflammation in the spinal cord plays a critical role in the pathogenesis of neuropathic pain. Chemokine CXCL9, CXCL10, and CXCL11 have been identified as a same subfamily chemokine which bind to CXC chemokine receptor 3 to exert functions. Our recent work found that CXCL10 is upregulated in spinal astrocytes after spinal nerve ligation (SNL) and acts on chemokine receptor CXCR3 on neurons to contribute to central sensitization and neuropathic pain, but less is known about CXCL9 and CXCL11 in the maintenance of neuropathic pain. Here, we report that CXCL9 and CXCL11, same as CXCL10, were increased in spinal astrocytes after SNL. Surprisingly, inhibition of CXCL9 or CXCL11 by spinal injection of shRNA lentivirus did not attenuate SNL-induced neuropathic pain. In addition, intrathecal injection of CXCL9 and CXCL11 did not produce hyperalgesia or allodynia behaviors, and neither of them induced ERK activation, a marker of central sensitization. Whole-cell patch clamp recording on spinal neurons showed that CXCL9 and CXCL11 enhanced both excitatory synaptic transmission and inhibitory synaptic transmission, whereas CXCL10 only produced an increase in excitatory synaptic transmission. These results suggest that, although the expression of CXCL9 and CXCL11 are increased after SNL, they may not contribute to the maintenance of neuropathic pain.